2021
DOI: 10.1128/mbio.00568-21
|View full text |Cite
|
Sign up to set email alerts
|

Early Emergence and Long-Term Persistence of HIV-Infected T-Cell Clones in Children

Abstract: Little is known about the emergence and persistence of human immunodeficiency virus (HIV)-infected T-cell clones in perinatally infected children. We analyzed peripheral blood mononuclear cells (PBMCs) for clonal expansion in 11 children who initiated antiretroviral therapy (ART) between 1.8 and 17.4 months of age and with viremia suppressed for 6 to 9 years. We obtained 8,662 HIV type 1 (HIV-1) integration sites from pre-ART samples and 1,861 sites from on-ART samples. Expanded clones of infected cells were d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 60 publications
1
15
0
2
Order By: Relevance
“…Previous studies have analyzed integration sites that arose in vivo before the initiation of ART ( 16 , 37 ) and then during ART treatment ( 12–14 , 16 , 37 , 48 , 66 ). Critically, however, the precise interplay among genic integration sites that arise during the initial wave of HIV-1 infection, which was modeled herein using in vitro datasets, with these patient-derived populations is not clearly understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have analyzed integration sites that arose in vivo before the initiation of ART ( 16 , 37 ) and then during ART treatment ( 12–14 , 16 , 37 , 48 , 66 ). Critically, however, the precise interplay among genic integration sites that arise during the initial wave of HIV-1 infection, which was modeled herein using in vitro datasets, with these patient-derived populations is not clearly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 integration site datasets derived from WT transformed and primary cells infected in vitro in this study, the following 8 were published previously: HEK293T #1 ( 20 , 27 ), HEK293T #3 ( 31 ), Jurkat #2 ( 40 ), Jurkat #3 ( 40 ), peripheral blood mononuclear cells (PBMCs) ( 47 , 48 ), monocyte-derived macrophages (MDM) ( 46 ), elite controller (EC) primary CD4+ T cell ( 49 ), and HIV negative primary CD4+ T cell ( 49 ) (see Supplementary Table S2 for numbers of integration sites as well as genomic DNA fragmentation and library construction methodologies). Matched HEK293T #1, HEK293T LKO, HEK293T CKO, and HEK293T double knockout (DKO) datasets were previously described ( 20 , 27 ), as were matched Jurkat #2, LKO Jurkat #1, and LKO Jurkat #2 datasets ( 40 ) ( Supplementary Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…In perinatally infected children in the CHER cohort, HIV-infected cell clones were detectable before ART initiation and remained detectable up to 9 years on suppressive treatment. In another study, a child who initiated treatment within the first week of life had a potential clone detected 7 hours after birth, suggesting that early ART alone does not interfere with the proliferation of infected cells [105,127]. In adults, clones expand to detectable levels by 4 weeks post-infection (Fiebig stage V) [128].…”
Section: Clonal Expansion Maintains the Reservoir In Treated Childrenmentioning
confidence: 98%
“…Rarely, the site of proviral integration in the host genome, particularly sites in genes responsible for cell growth and survival, may drive the proliferation of infected cell clones or, at least, promote their survival [116,120,124,130,131]. In children, selection for integrations in STAT5B and BACH2 was observed both prior to and during long-term ART [127]. However, antigenic stimulus is likely the greatest contributor to the persistence of infected clones.…”
Section: Clonal Expansion Maintains the Reservoir In Treated Childrenmentioning
confidence: 99%
“…The integration into these genes may also favor certain CD4 T cell subsets, such as T regulatory cells ( 15 ). Bale and Katusiime et al ( 16 ) have shown that these patterns also appear in the setting of early treated perinatal infection, suggesting that integrated provirus in this region also confers an evolutionary advantage even in the context of an immature immune system. The epigenetic landscape of these infected cells is also drastically different in infants ( 17 ), and this may in turn affect integration site and the level of epigenetic repression under ART.…”
Section: Commentarymentioning
confidence: 97%